Dismantling of the dominant European discourse in the poetry of Jeanine Leane - Čerče, Danica (Penerbit Universiti Kebangsaan Malaysia, 2020)
Until very recently a marginalised voice in Australian literary studies, Australian Indigenous literature has obtained an important role in the articulation of Indigenous peoples’ political thought, constituting an indictment of white Australian racism, a recuperation of neglected Aboriginal history, and a call for change. Based on the premise that literature can play an important role in both maintaining and disrupting the exercise of power, and written against the backdrop of post-colonial theory, the article deals with the collection of poems Dark Secrets: After Dreaming A.D. 1987-1961 (2010) by the contemporary Australian Indigenous author Jeanine Leane. Taking Leane’s poetry as exemplary of post-colonial textual resistance to colonialist representations, the article shows how the poet, relying on the “transgenerational blood memory” intervenes in the presupposed irreducible division between subjugating and subjugated cultures, that is, the assumptions about whiteness as a static privilege-granting category and a system of dominance upon which the logic of coloniality often stands. I argue that, by mobilising various techniques and strategies to challenge the reproduction of whiteness and affirm Indigenous Australians’ authentic, rather than an imposed cultural personality, Leane’s verse performs both personal and collective empowerment of Indigenous Australians, and represents an important site for the renegotiation of inter-racial relationships.